Development of operation strategy for PV- fuel cell hybrid power system to maximize efficiency and minimize stress - Indriawati, Katherin; Nawangsih, Nawangsih; Ekatiara, Cindy Reviko (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
This study explores the development of an energy management strategy (EMS) using a modified external energy management strategy (EEMS) for a hybrid PV-fuel cell power system. The primary aim was to address efficiency challenges and reduce the premature aging of fuel cells, batteries, and supercapacitors (SCs) caused by excessive stress. Incorporating photovoltaic (PV) energy as an additional renewable energy source (RES) has proven to improve the efficiency of the hybrid system. The EEMS-based strategy reduces hydrogen consumption by prioritizing the energy supply from the battery and SC. However, the traditional EEMS approach introduces chattering phenomena that can negatively impact system lifespan. By modifying the EEMS optimization problem, the modified EEMS effectively mitigates chattering, maintaining the battery's state of charge (SOC) and the DC bus voltage within specified ranges, while also reducing stress on the battery and SC. The results demonstrate a significant enhancement in both system performance and efficiency.